THE EFFECTIVENESS OF QUANTUM READING MODEL BY PRINTING MEDIA WITH YEN BASIS IN READING CONCEPT LEARNING TO STUDENTS OF GRADE 4TH IN SUMBER REGENCY, CIREBON, SCHOOL ACADEMIC YEAR 2013/2014 - Mintarsih Danureja; Tati Hartati (Program Studi Pendidikan Bahasa Indonesia Pascasarjana UGJ, 2014)
This research is intended to know the effectiveness of quantum reading model by printing media with yen basis in reading concept learning to students of grade 4th elementary school. The problems are: profile of students reading concept competences, the learning process of reading concept, the learning process of reading concept by quantum reading model by printing media with yen basis, the effectiveness of quantum reading model by printing media with yen basis in reading concept learning, and students response of quantum reading model by printing media with yen basis.The trouble-shooting is by use quantum reading model by printing media with yen basis by assumption: if students need to do something therefore will be easily to motivate them in learning and get a better result.Population in this research is Grade 4th Students of elementary school at Sumber Regency, Cirebon. The sample is determined by purposive sampling. The objects in this research are quantum reading model by printing media with yen basis and students reading concept competences. Instruments in this research are sheets of questionnaire, sheets of learning observation, and reading concept competence test. Data that are collected are learning process and data of students reading concept competences. Collected data are analyzed by descriptive statistic analyze.Result of this research are: (1) the competences of students reading concept are good, (2) the learning process are done with students actively, (3) quantum reading model by printing media with yen basis can increase students activity and learning result, (4) quantum reading model by printing media with yen basis is effective to use in reading concept learning, and (5) the students response to reading concept learning by use quantum reading model by printing media with yen basis is very good.Base on the result of this research, get to be proposed for teacher to use quantum reading model by printing media with yen basis to increase students reading concept competence as one of alternative technique in learning, because it is able to motivate, grow the students interest, and increase students creativities to increase students reading concept competences.